PENINGKATAN PEMAHAMAN METODE TAFSIR BI AL-MA’TSÛR PADA MAHASISWA UNIVERSITAS PTIQ JAKARTA - Kerwanto Kerwanto; Rahman Apandi; Azmi Ismail; EE Junaedi Sastradiharja; Zakiyatul Fitriyah (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Tafsir bi al-ma’tsûr is said tobe the most correct and safest interpretation methode to stay awake from slipping because it adheres to authoritative sources of interpretation. In its use, the term interpretation bi al-ma’tsûr is often used as an opponent for the interpretation of bi al-ra’yi (with reason). However, the dichotomy between the two becomes ambiguous, because of the overlap in the use of the two terms. This can be seen from the influence of the reasoning of the interpreters who are always present in interpreting the Qur'an even though they adhere to the traditions of interpretation, and the use of the term interpretation bi al-ma’tsûr does not yet have a clear procedur